Analisis Tafsir Ayat-Ayat tentang Gaya Pengasuhan Ayah dalam Membina Akhlak Keluarga Perspektif Ibnu Qayyim al-Jauziyyah: Analysis of Qur’anic Exegesis on Fatherly Parenting Styles in Cultivating Family Morals from the Perspective of Ibn Qayyim al-Jawziyyah - Ibra Asy-syaula Adha Mujiono; Muhammad Aufa (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2026)
The role of fathers in fostering moral character within the family holds a strategic position in Islam; however, studies that examine this issue in depth through the perspective of classical Qur’anic exegesis remain relatively limited. Therefore, this study discusses the role of fathers in moral education within the family based on the interpretive perspective of Ibn Qayyim al-Jawziyyah. This study aims to examine Ibn Qayyim’s views on the responsibility of fathers as qawwam (leaders) in the family and to analyze paternal parenting styles in shaping family morality based on Qur’anic verses. This research employs a qualitative approach using library research and a descriptive-analytical method by examining Ibn Qayyim’s works and relevant Qur’anic verses. The findings indicate that Ibn Qayyim views the father as a qawwam who bears responsibility for family leadership, particularly in the aspect of moral education. The educational methods emphasized include instruction, habituation, and exemplary conduct. Interpretations of Q.S. an-Nisā’ (4):34, Q.S. at-Taḥrīm (66):6, Q.S. ar-Rūm (30):21, and Q.S. Luqmān (31):12–19 reveal that paternal leadership is characterized by firmness, responsibility in providing sustenance, mutual admonition, and an orientation toward establishing a family grounded in sakinah, mawaddah, and rahmah. Furthermore, moral development encompasses the inculcation of monotheism, filial piety (birr al-wālidayn), self-awareness, the establishment of prayer, enjoining good and forbidding evil, patience, humility (tawāḍu‘), and proper etiquette in speech. In conclusion, Ibn Qayyim al-Jawziyyah’s concept of leadership and family education remains relevant as a foundational framework for shaping the noble character of Muslim family members.